(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
The use of oral history as a methodological tool in this research has allowed us to recovery, interpretation and dissemination of social experiences of women in relation to the existing cultural heritage in museums of the Province of Buenos Aires. Using this method provided us the construction of historical sources by recovering the memory of the women interviewed involving all / as those / as not falling within the dominant historical narrative and absent in traditional sources.